Pottery MSMEs in Kasongan, Bantul, and Behavioral Intention to Use E-Wallet - Laksmi, Ayu Chairina; Piniji, Lintang Sekar (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The purpose of this study is to describe pottery MSMEs in Kasongan, Bantul and their behavioral intention to use e-wallet. E-wallet is an electronic wallet that helps speed up transaction activities of its users. Technological updates make it easier for people to carry out financial activities wherever they are and at any time and using e-wallets will make it easier for their users to improve and update their business transactions. The population in this study is pottery MSMEs players in Kasongan, Bantul who have not used e-wallet before. This study uses qualitative research methods and employs semi-structured interviews to collect data from 10 pottery MSMEs players in Kasongan, Bantul. The results of this study indicate that pottery MSMEs players in Kasongan, Bantul, are still limited in terms of technology use and e-wallet use for their business. However, the findings of this study also show that pottery MSMEs players in Kasongan, Bantul, have the behavioral intention to use e-wallet to facilitate their business transactions.